Corporate Diversification and Firm Performance: Evidence from Asian Hotel Industry - Ooi, Chai Aun; Hooy, Chee Wooi; Mat Som, Ahmad Puad (EDP Sciences, 2014)
The unstable environment of hotel industry which is driven by the fluctuation of tourism demand has motivated this study to look into the best diversification strategy for firm performance betterment. 42 hotel firms are investigated across 4 Asian economies, from year 2001 to 2012. Our results suggest that unrelated industrial diversification is the only alternative to improve hotel firm performance. Unrelated international diversification instead has a significant negative effect towards firm performance. Our results further show that board of directors implies a significant link to the relationship between diversification and firm performance, only in a crisis period.